PD-1/PD-L1 Pathway Modulates Macrophage Susceptibility to Mycobacterium tuberculosis Specific CD8+ T cell Induced Death - Suarez, Guadalupe Verónica (2019)
CD8+T cells contribute to tuberculosis (TB) infection control by inducing death of infected macrophages. Mycobacterium tuberculosis (Mtb) infection is associated with increased PD-1/PD-L1 expression and alternative activation of macrophages. We aimed to study the role of PD-1 pathway and macrophage polarization on Mtb-specifc CD8+T cell-induced macrophage death. We observed that both PD-L1 on CD14+ cells and PD-1 on CD8+T cells were highly expressed at the site of infection in pleurisy TB patients’ efusion samples (PEMC). Moreover, a signifcant increase in CD8+T cells’ Mtb-specifc degranulation from TB-PEMC vs. TB-PBMC was observed, which correlated with PD-1 and PDL-1 expression. In an in vitro model, M1 macrophages were more susceptible to Mtb-specifc CD8+T cells’ cytotoxicity compared to M2a macrophages and involved the transfer of cytolytic efector molecules from CD8+T lymphocytes to target cells. Additionally, PD-L1 blocking signifcantly increased the in vitro Ag-specifc CD8+T cell cytotoxicity against IFN-γ-activated macrophages but had no efect over cytotoxicity on IL-4 or IL-10-activated macrophages. Interestingly, PD-L1 blocking enhanced Mtbspecifc CD8+ T cell killing of CD14+ cells from human tuberculous pleural efusion samples. Our data indicate that PD-1/PD-L1 pathway modulates antigen-specifc cytotoxicity against M1 targets in-vitro and encourage the exploration of checkpoint blockade as new adjuvant for TB therapies.